The early Muslim discussion on the problem of the divine attributes with an emphasis on the Mu'tazilites - Moris, Megawati (IIUM Press, International Islamic University Malaysia, 2020)
Abstract This paper discusses on the problem of the Divine Attributes by the early Muslim Kalām scholars focusing on the Mu„tazilah. There are three different views on the reasons which led to the discussion. They can be grouped into internal, external and both internal and external factors. The early discussion on this subject can also be viewed from three broad positions. The first group is the rationalistic Muʿtazilah view of emphasizing God‟s transcendence and incomparability (tanzīh) above all Attributes; secondly, the Attributists (Ṣifātī), Anthropomorphists (Mujassimīn) and Comparers (Mushabbihīn) who maintained that God possesses all the Attributes mentioned in the Qur‟ān and they must be taken literally; and the third which is the middle position between these two groups represented by the Ashʿarī school. This paper investigates the definition and origins of the concept of Ṣifāt Allāh and also the thought of three different thinkers in the Muʿtazilah School to show there are some differences between their views. The paper concludes by reiterating that Allāh provides man the means by which He can be known not only philosophically and theologically but more importantly spiritually by drawing close to Him, and this can be achieved by remembering and calling upon His Names. Keywords:Kalām, Divine Attributes, Mu„tazilah, transcendence, anthropomorphism.